Antibody Response to SARS-CoV-2 Vaccines in People with Severe Obesity - DİNÇ, HARİKA ÖYKÜ; KARA, ZEHRA; Akcin, Ruveyda; DEMİR, Ahmet Numan; DİNÇ, HARİKA ÖYKÜ; Taskin, Halit Eren; KOCAZEYBEK, BEKİR SAMİ; YUMUK, VOLKAN DEMİRHAN (My University, 2022)
Aim: Obesity is a disease complicating the course of COVID-19 and SARS-CoV-2 vaccine effectiveness in adults with obesity may be compromised. Our aim is to investigate the spike-protein receptor-binding domain antibody titers against BNT162b2 mRNA and inactivated SARS-CoV-2 (CoronaVac) vaccines in people with severe obesity. It is anticipated that the results to be obtained may provide invaluable information about future SARS-CoV-2 vaccination strategies in this vulnerable population. Methods: A total of 124 consecutive patients with severe obesity (age > 18 years, BMI ≥ 40 kg/m2) presenting between August and November 2021 were enrolled. The normal weight control group (age > 18, BMI 18.5-24.9 kg/m2) was recruited from 166 subjects who visited the vaccination unit. SARS-CoV-2 spike-protein antibody titers were measured in patients with severe obesity and in normal weight controls who received two doses of BNT162b2, or CoronaVac vaccines. SARS-CoV-2 IgG Nucleocapsid Protein antibody (NCP Ab) testing was performed to discover prior SARS-CoV-2 infection. Blood samples were taken from individuals at 4th week and after 2nd dose of vaccination. SARS-CoV-2 IgG antibody titers were determined by quantitative serological methods. Results: A total of 290 individuals (220 female, 70 male) who have received two doses of BNT162b2 or CoronaVac vaccines were enrolled in the study. Seventy had prior SARS-CoV-2 infection. In 220 subjects (non-prior infection) vaccinated with BNT162b2 or CoronaVac, the antibody titers against SARS-CoV-2 spike antigen of patients with severe obesity were significantly lower than normal weight controls (p = 0.001, p = 0.001 respectively). In seventy subjects with prior SARS-CoV-2 infection, spike antigen antibody titers in patients with severe obesity, vaccinated with BNT162b2 or CoronaVac, were not significantly different from normal weight controls (p = 0.1, p = 0.1 respectively). In patients with severe obesity, with and without prior SARS-CoV-2 infection, spike antigen antibody levels of those vaccinated with BNT162b2 were found to be significantly higher than those vaccinated with CoronaVac (p = 0.043, p < 0.001 respectively). Conclusion: Patients with severe obesity generated significantly reduced antibody titers against SARS-CoV-2 spike antigen after CoronaVac and BNT162b2 vaccines compared to people with normal weight. Antibody levels in patients with severe obesity vaccinated with BNT162b2 were found to be significantly higher than those vaccinated with CoronaVac. People living with severe obesity should be prioritized for COVID-19 vaccination and BNT162b2 vaccine may be recommended for this vulnerable population.
Keywords: Antibody response; Severe obesity; Vaccines